The procurement game plan : winning strategies and techniques for supply management professionals - Dominick, Charles, 1972-; Lunney, Soheila R., 1952- (J. Ross Publishing, Inc., 2022)
"The second edition of this best-selling guide provides an updated easy-to-follow game plan with strategies for procurement and supply management professionals to improve supplier relationships, secure measurable cost reductions, build a more resilient supply chain, integrate social responsibility into procurement activities, achieve operational effectiveness and efficiency, and positively impact margins and competitiveness for their organizations. The Procurement Game Plan offers the guidance needed to take the procurement professional's career and department to the next level. This tool is ideal for self-learning, training, and classroom instruction. It is also an entertaining read due to the analogies and contrasts to various sports"-- Provided by publisher.
Keywords: Industrial procurement.; Purchasing.; Business logistics.; elektronické knihy; electronic books